HUBUNGAN SELF EFFICACY DENGAN TINGGINYA GAYA HIDUP KURANG SEHAT PADA PASIEN HIPERTENSI DENGAN PENDEKATAN KONSEP MODEL KEPERAWATAN ALBERT BANDURA - Nisfil Mufidah; Rahmad Wahyudi; Sitti Sulaihah; Diniyah Diniyah (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2022)
Hypertension is the main factor as the number one cause of death in the world or known as the silent killer. One of the problems that occur in hypertensive patients at the UPT Kedungdung Health Center, Bangkalan Regency, is the height of an unhealthy lifestyle. One of the factors that affect self-efficacy. This study aims to analyze the relationship between Self Efficacy and lifestyle in hypertensive patients with the Albert Bandura nursing model concept approach. The research design used analytics with the cross-sectional approach. Research variables are self-efficacy and lifestyle. The population of 49 hypertension patients in the working area of ​​the Kedungdung Health Center with the number of samples taken is 44. The sampling technique uses probability sampling with the Simple Random Sampling technique. Data collection techniques using self-efficacy and lifestyle questionnaires. Statistical test using Spearman Rank test with (a=0.05). This research has been carried out Ethical clearance tested by the KEPK STIKes team, NgudiaHusada Madura. The results showed that based on the Spearman Rank statistical test with test results (p = 0.000) < (a = 0.05). So it can be concluded that there was a relationship between Self Efficacy and lifestyle in hypertensive patients with the Albert Bandura nursing model concept approach in the working area of ​​the Kedungdung Health Center, Bangkalan Regency. It is recommended that health workers at the UPT Kedungdung Public Health Center pay attention to the self-efficacy of hypertensive patients so that this can affect the lifestyle of hypertensive patients whose ultimate goal is to reduce hypertension